2012
DOI: 10.1074/jbc.m111.328054
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-449 and MicroRNA-34b/c Function Redundantly in Murine Testes by Targeting E2F Transcription Factor-Retinoblastoma Protein (E2F-pRb) Pathway

Abstract: Background: MicroRNAs (miRNAs) are post-transcriptional regulators involved in the regulation of gene expression. Results: miR-449 and miR-34b/c function redundantly in male germ cells. Conclusion: CREM-SOX5-mediated miR-449 expression regulates male germ cell development by targeting the E2F-pRb pathway. Significance: Upstream regulators of miR-449 expression and a redundant role between miR-449 and miR-34b/c in the control of male germ cell development were revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
191
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(211 citation statements)
references
References 60 publications
13
191
0
2
Order By: Relevance
“…These findings suggest that miRNAs necessary to confer spermatogonial differentiation may be synthesized by non-canonical enzymes, and the underlying mechanism remains to be elucidated. It has recently been found that miR-449 is predominantly expressed in mouse testes and it is mainly located in spermatocytes and spermatids (Bao et al 2012, Wu et al 2014. Interestingly, miR-34b and miR-34c have been found to resemble the 'seed' sequence of miR-449.…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that miRNAs necessary to confer spermatogonial differentiation may be synthesized by non-canonical enzymes, and the underlying mechanism remains to be elucidated. It has recently been found that miR-449 is predominantly expressed in mouse testes and it is mainly located in spermatocytes and spermatids (Bao et al 2012, Wu et al 2014. Interestingly, miR-34b and miR-34c have been found to resemble the 'seed' sequence of miR-449.…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
“…Interestingly, miR-34b and miR-34c have been found to resemble the 'seed' sequence of miR-449. Coincidentally, miR-34b and miR-34c exhibit a similar effect to that of miR-449 during the development of male germ cells and spermatogenesis (Bouhallier et al 2010, Bao et al 2012, Wu et al 2014. Individual deficiency in miR-34b/c or miR-449 appears to have no obvious effect; however, simultaneous inactivation of miR-34b/34c and miR-449 leads to mouse oligoasthenoteratozoospermia (Wu et al 2014), implicating that double or triple knockout approach of miRNAs is needed to obtain the phenotype for certain miRNAs.…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
“…Noncoding RNA encompass a variety of discrete entities, including micro RNA (miRNA), ultra conserved long non-coding RNA and pyknons. While several miRNA species are regulated via E2F and RB, the mechanisms coordinating such altered expression of miRNA, [11][12][13][14] the targets and overall mode of regulation has remained obscure relative to coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the present study, the data regarding adenocarcinoma was scattered across various databases, including TransmiR (13), computational predicted methods (42), experimentally validated databases (15,16), miRBase (17), the KEGG pathway database (18), the miR2Disease database (19), the GeneCards database (20) and numerous relevant studies (13,(17)(18)(19)(20). The analysis and use of this data is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that TFs and miRNA may regulate genes (8) and miRNA may regulate target genes (10). In addition, the data of numerous studies have been combined to form various databases, including TransmiR (13), computational predicted methods (14), experimentally validated databases (15,16), miRBase (17), the KEGG pathway database (18), the miR2Disease database (19) and the GeneCards database (20). In these databases, a large amount of data may be found, which was the basis for the present study.…”
Section: Introductionmentioning
confidence: 99%